Non-enzymatic Determination of Glucose in Artificial Urine Using 3D-µPADs through Silver Nanoparticles Formation - Fahmi, Ahmad Luthfi; 'Aisy, Kamila Rohadatul; Wulandari, Ika Oktavia; Sulistyarti, Hermin; Sabarudin, Akhmad (Indonesian Journal of Chemistry, 2024)
Patients with diabetes often experience blood glucose fluctuations, making monitoring crucial. Traditional blood sampling methods pose risks of infection and pain. An alternative non-invasive approach using urine tests has been explored. Recent studies highlight microfluidic paper-based analytical devices (µPADs) as convenient, simple, and easily fabricated tools for non-invasive glucose measurement. This study aims to develop a concept of measuring glucose in artificial urine using 3D-µPADs in a non-enzymatic manner by utilizing glucose as a reducing agent for silver nanoparticle (AgNPs) formation. Embedding three-dimensional connectors in µPADs links the sample and detection zones to limit reagent mixing and improve glucose detection resolution. The optimal conditions were NaOH 10 M, starch 1%, and AgNO3 30 mM, with sample and detection zone volumes of 10 and 9 µL, respectively. The fifth reaction sequence involved AgNO3 in the detection zone and a solution of glucose, NaOH, and starch in the sample zone at 1:1:1 volume ratio. The reagent drying time was 15 min, with immobilization once and reaction time of 9 min. The method showed excellent linearity (R2 = 0.9905), precision (%RSD = 4.27%), accuracy (77.32–92.58%), and limit of detection (11.11 mg/dL).